Manajemen Pengembangan Penilaian Pendidikan Karakter Dalam Kurikulum Merdeka Belajar Di SMA 1 Rancaekek Bandung - Isnaini, Putri; Rosiana, Indah; Salsabila, Aulia Nursekha; Supendi, Pepen (LP2M STAI Miftahul 'Ula (STAIM) Nganjuk, 2025)
Character education is a crucial component of the Merdeka Belajar Curriculum to develop a generation with integrity and competitiveness. This study aims to develop the management of character education assessment at SMA 1 Rancaekek through a holistic approach oriented toward the Pancasila Student Profile. The position of this research lies in aligning character education assessment with the principles of the Merdeka Curriculum. The method used is qualitative-descriptive, with data collection procedures including observation, interviews, and document analysis. The core findings indicate that character education assessment management involves integrated planning, implementation based on authentic assessment, and evaluation through collaboration between teachers, students, and parents. The results conclude that an effective character education assessment system can improve the quality of learning and strengthen students' character, offering recommendations for other schools to optimally implement the Merdeka Curriculum.